Mechanisms and Pharmacotherapy for Ethanol-Responsive Movement Disorders - Wu, Jingying; Tang, Huidong; Chen, Shengdi; Cao, Li (Frontiers in Neurology, 2020)
Ethanol-responsive movement disorders are a group of movement disorders of which clinical manifestation could receive significant improvement after ethanol intake, including essential tremor, myoclonus dystonia and some other hyperkinesia. Emerging evidence supports that the sensitivity of these conditions to ethanol might be attributed to similar anatomical targets and pathophysiologic mechanisms. Cerebellum and cerebellum-related networks play a critical role in these disease. Suppress of inhibitory neurotransmission and hyper-excitability of these regions are the key points for pathogenesis. GABA pathways, the main inhibitory system involved in these regions, were firstly linked to pathogenesis of these diseases, and GABAA receptors and GABAB receptors play critical roles in ethanol-responsiveness. Moreover, impairment of low-voltage-activated calcium channels, which were considered as a contributor to oscillation activity of nervous system, also participate in the sensitivity of ethanol in relevant disease. Glutamate transporters and receptors that are closely associate with GABA pathways, are the action sites for ethanol as well. Accordingly, alternative medicines aiming at these shared mechanisms appeared subsequently to mimic ethanol-like effects with less liability, and some of them have achieved positive effects on different diseases with well tolerance. However, more clinical trials with a large sample and long-term follow-ups are needed for pragmatic use of these medicines, and further investigations on mechanisms will continue to deepen the understanding of these diseases and also accelerate the discovery of ideal treatment.